PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X2 DALAM MATERI SENAM IRAMA DI SMAN 1 BANJARBARU - Fauzi, Muhammad; Indah, Eka Purnama; Sani, Abdullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was conducted in response to the unsatisfactory learning outcomes of students in rhythmic gymnastics lessons in Class X2 of SMAN 1 Banjarbaru. Preliminary observations indicated that a considerable number of students failed to meet the Minimum Mastery Criterion (MMC) of 75. This situation was influenced by the predominance of teacher-centered instruction, which limited students’ opportunities to actively participate, collaborate, and develop confidence during learning activities. The purpose of this study was to enhance students’ learning outcomes through the application of the Project-Based Learning (PjBL) model. This study employed a collaborative Classroom Action Research (CAR) approach consisting of two cycles. The participants were 34 students from Class X2 of SMAN 1 Banjarbaru. Data were gathered through classroom observations, learning achievement tests, and documentation. The collected data were analyzed descriptively by comparing the results obtained in the pre-cycle, Cycle I, and Cycle II stages. The findings demonstrated that the implementation of Project-Based Learning contributed positively to students’ achievement in rhythmic gymnastics. Learning mastery improved from 58.82% in the pre-cycle stage with an average score of 69.41, to 79.41% in Cycle I with an average score of 78.24, and further increased to 91.18% in Cycle II with an average score of 86.47. Moreover, the learning model encouraged greater student participation, creativity, teamwork, discipline, and self-confidence throughout the instructional process. Therefore, it can be concluded that Project-Based Learning is an effective instructional model for improving students’ learning outcomes in rhythmic gymnastics'